Inoculation of plant growth promoting rhizobia in Sudan grass (Sorghum × sudanense (Piper) Stapf cv. Sudanense) and millet (Pennisetum glaucum (L.) R.Br. cv. BRS1501) (2018)
Rhizobia are able to increase yield of non-leguminous species through production of phyto-stimulating substances. This study aimed to evaluate the inoculation effect of rhizobia UFRGS Lc348 and VP16 on millet and Sudan grass yield and germination, and verify the enrichment effect of culture medium with tryptophan, which leads on the rhizobium/plant interaction. Experiments in vitro and greenhouse conditions were conducted. In millet, the inoculation with VP16 grown in culture medium with or without tryptophan induces greater length of hypocotyl and epicotyl under in vitro conditions. UFRGS Lc348 treatment induces longer hypocotyls of millet under in vitro conditions. No effects were observed with the millet inoculation in greenhouse. In Sudan grass, inoculation with VP16 enriched with tryptophan increased dry matter in shoots of adult plants. In millet seedlings had achieved an increasing in elongation in vitro conditions, which could represent an adaptive advantage in the search for water and nutrients in the rhizospheric environment during the initial growth of millet. Similarly, if verified in field conditions, Sudan grass had achieved an increasing in greenhouse conditions with the inoculation of tryptophan-enriched VP16, which could be correlated with a significant gain in crop yield. Therefore, these relationships between tryptophan-enriched VP16 and Sudan grass should be verified in subsequent studies under field conditions.